The Digital Economic Ecosystem in Vietnam - Tran, Trang Mai (Journal of Multidisciplinary Science: MIKAILALSYS, 2023)
Since the early 2000s, digitalization and the digital economy have developed rapidly and rapidly changed all aspects of social life. Digital platform ecosystems in Vietnam are still in their early stages of development, but they are growing rapidly. These digital platforms are playing an increasingly important role in the Vietnamese economy. They are driving innovation, economic growth, and job creation. This article will analyze some of the current development status of the digital economic ecosystem in Vietnam: the advantages as well as the difficulties and challenges that Vietnam will face. The article will provide some policy suggestions for Vietnam in developing the digital economic ecosystem from these analyses.